2018
DOI: 10.1088/1757-899x/342/1/012034
|View full text |Cite
|
Sign up to set email alerts
|

Performance of magnetorheological elastomer based green epoxidized natural rubber/sucrose acetate isobutyrate hybrid matrix

Abstract: Abstract. This study introduces a sucrose acetate isobutyrate (SAIB) as a novel additive of magnetorheological elastomers (MREs). The MREs utilized an epoxidized natural rubber (ENR) as the matrix and carbonyl iron particles (CIPs) as their filler. The CIPs were fixed at 60 wt%. The viscosity of the compound was observed using a viscometer. Meanwhile, the microstructures were observed by using field emission scanning electron microscope (FESEM). Rheological properties regarding shear storage modulus were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The MRE is an excellent potential candidate for smart devices used in a variety of engineering fields, especially in fields involving vibration isolations. Many researchers proposed many vibration isolators with MREs based [2], [5], [9], [12]- [14]. Previous studies have shown potential MREs applications for vibration isolation control.…”
Section: Introductionmentioning
confidence: 99%
“…The MRE is an excellent potential candidate for smart devices used in a variety of engineering fields, especially in fields involving vibration isolations. Many researchers proposed many vibration isolators with MREs based [2], [5], [9], [12]- [14]. Previous studies have shown potential MREs applications for vibration isolation control.…”
Section: Introductionmentioning
confidence: 99%